Effect of Resin Infiltrant and Fluoride Varnish on the Microhardness of Artificially Induced Enamel Lesion: An In Vitro Study - Mohammed, Zahraa; Aldulaimy, Dunia A. (European Journal of General Dentistry, 2025)
This study aims to assess the effects of resin infiltrant in comparison to fluoride varnish on the microhardness of artificially induced enamel lesions at various storage time intervals.In this study, 36 tooth samples were assigned to two groups (n = 18): resin infiltrant and fluoride varnish. The groups were further subdivided into three distinct subgroups (n = 6) based on the storage time in artificial saliva (1-week, 2-week, and 4-week). All samples were subjected to the pH cycling procedure to induce the formation of white spot lesions. The first group received resin infiltrant treatment, while the second group was treated with fluoride varnish. Microhardness assessments were performed at the baseline, subsequent to the pH cycling procedure, and following 1-week, 2-week, and 4-week intervals from the initial application of treatment agents.Statistical analysis was performed using the paired t-test to evaluate within-group differences across the three time points for each material. Subsequently, an independent t-test was employed to assess between-group differences following treatment.Statistical analysis of mean microhardness values following the pH cycling procedure revealed a significant reduction in enamel microhardness in both groups (p = 0.001). Although no significant differences were observed between the two materials during the first two time intervals, a significant difference was detected in the third interval.Both infiltrant and fluoride varnish enhanced enamel microhardness, with resin infiltrant demonstrating a more sustained effect over time.
Keywords: resin infiltrant; fluoride varnish; microhardness; white spot lesions; minimally invasive dentistry